Phosphate-based glass microspheres for bone repair and localised chemotherapy and radiotherapy treatment of bone cancers - Milborne, Ben (2023)
Phosphate-based glasses (PBGs) are hugely promising materials for bone repair and regeneration as they can be formulated to be compositionally similar to the inorganic component of bone. Alterations to PBG formulations can be made to tailor their degradation rates and subsequent release of biotherapeutic ions to induce cellular responses, such as osteogenesis. In this work, novel invert-PBGs in the series xP2O5·(56-x)CaO·24MgO·20Na2O (mol%), where x is 40, 35, 32.5 and 30, were formulated to contain pyro (Q1) and orthophosphate (Q0) species. These PBGs were then processed into highly porous microspheres (PMS) via a flame spheroidisation process developed within the research group. Compositional and structural analysis using EDX and 31P-MAS NMR analysis revealed significant depolymerisation had occurred with reducing phosphate content, which increased further when PBGs were processed into PMS. A decrease from 50% to 0% of Q2 species and increase from 6% to 35% of Q0 species was observed for the PMS when the phosphate content decreased from 40 to 30 mol%. Ion release studies also revealed up to a 4-fold decrease in cations and an 8-fold decrease in phosphate anions released with decreasing phosphate content. In vitro bioactivity studies revealed that the orthophosphate rich PMS had favourable bioactivity responses after 28 days of immersion in SBF. Indirect and direct cell culture studies confirmed that the PMS were cytocompatible and supported cell growth and proliferation over 7 days of culture. The P30 PMS with ~65% pyro and ~35% ortho phosphate content revealed the most favourable properties and was proposed to be highly suitable for bone repair and regeneration, especially for orthobiologic applications owing to their highly porous morphology. Doxorubicin (DOX) was used as a model drug to assess its loading and release kinetics from porous phosphate-based glass microspheres to ascertain their suitability for localised drug delivery for the treatment of bone cancers. P40 PMS revealed a DOX loading efficiency of 55%, which was significantly greater than P30 PMS at 29.1%. Both P40 and P30 PMS released more DOX in phosphate buffered saline (PBS) at pH 5 as compared to release at pH 7.4. P40 PMS released 57% of DOX at pH 5 over a 48-hour period, whereas P30 PMS only released 15% of DOX. A pH-responsive DOX release in a more acidic environment suggests that the chemotherapeutic delivery and efficacy properties may lead to increased drug release within tumour tissues. Internal radiotherapy has been shown to be an effective treatment modality to destroy cancerous tissues and is usually achieved by the placement of radioactive sources at the tumour site. In this work, a novel processing method was established to combine yttrium oxide (Y2O3) with P40 phosphate glass particles to form uniform, solid microspheres containing very high yttrium levels via our flame spheroidisation process. The 30Y (~15 mol% Y2O3) and 50Y microspheres (~39 mol% Y2O3) had equivalent and superior yttrium content in comparison to clinically available microspheres used for internal radiotherapy (i.e., Therasphere®). The yttrium-containing microspheres formed were shown to be glass-ceramics, with crystalline phases present but with all elements homogenously distributed throughout the microspheres. Increasing yttrium addition resulted in increased durability of the microspheres, with 50Y microspheres revealing a 10-fold decrease in the release rate of some ions compared to P40 solid microspheres. Indirect and direct cell culture studies confirmed that the 30Y and 50Y microspheres were cytocompatible and supported cell growth and proliferation over 7 days of culture. No significant difference was observed in the metabolic and ALP activity for MG63s for both 30Y and 50Y microspheres from both indirect and direct cell culture studies. Yttrium was incorporated into the phosphate-based microspheres at a level that had not previously been achieved or observed from the literature studies and were shown to support bone cell attachment and growth. A high yttrium content could enable more radiation to be delivered per dose of microspheres, resulting in shorter neutron activation times which could prove beneficial for logistical issues associated with transportation of the biomaterials following nuclear activation. The radionuclide holmium-166 (166Ho) which is comparable to yttrium-90 (90Y) in that it emits β-radiation with a similar tissue penetration range and a significantly reduced half-life of 26.8 hours, was also investigated. The beneficial paramagnetic properties and density of 166Ho indicates that 166Ho-doped materials could be visualised through clinical imaging techniques, whilst simultaneously delivering a therapeutic dose of radiation. In this work, solid holmium-containing microspheres were similarly produced via the flame spheroidisation process using holmium oxide (Ho2O3) and P40 phosphate glass particles. The glass-ceramic microspheres produced had equivalent (30H: ~17mol% Ho2O3) and superior (50H: ~30mol% Ho2O3) holmium content in comparison to clinically used yttrium-doped microspheres (i.e. Therasphere®). Analogous to yttrium containing microspheres, elevated holmium content resulted in topographically unique features on the surface of some 50H microspheres. This increased holmium content resulted in significantly reduced ion release rates for all the ions and the holmium-microspheres did not show evidence of bioactivity. However, in vitro indirect and direct cell culture studies demonstrated their cytocompatibility. No significant difference was observed in the metabolic and ALP activity of MG63 cells for 30H and 50H microspheres in both the indirect and direct cell culture methods. This study appears to be the first to demonstrate microspheres containing high levels of holmium content that can also facilitate direct cell growth and proliferation of human osteoblast-like cells. The microspheres developed are therefore hugely promising biomaterials for both drug delivery and internal radiotherapy applications, as well as for promoting bone repair and regeneration at damaged sites. High holmium content could also result in higher specific activity per microsphere to increase radiotherapy delivery whilst also promoting higher visibility via imaging modalities.